Reingeniería de la página WEB existente en el GAD (Gobierno Autónomo Descentralizado) parroquial de Santa Fé del cantón Guaranda, año 2018-2019 - Gaybor Lara, Freddy Oswaldo (2019)
The present case analysis arises because the institution has identified the need to maintain a web page according to current requirements, given that in these times the use of technology allows authorities to provide a better service to citizens and be in contact with it; An obligation of entities, organizations or institutions of public or private law that are related to the state is: disseminate information about them without a cost based on the principle of openness and publicity of their actions through the implementation of web pages, where it should be exposed: the structural organic, goals, objectives, complete directory, remunerations per position, the services offered, hours of service, full text of contracts, information on the annual budget, results of audits, information on pre- contractual processes, contractual , of adjudication and liquidation, of the contracting of works, acquisition of goods, provision of services, commercial leases, etc., that allow to know of the management carried out by the authorities fulfilling the postulate that Access to public information is a right of the people guaranteed by the State, in relation to what has already been and because within the Parish Council of Santa Fé an obsolete website is maintained because it was designed and never given maintenance, the exposed information is outdated to see this reality the present case analysis through the redesign of the website seeks to enforce the right to public information held by each of the people of this parish, for which it was necessary to use the RAP methodology called rapid web application development this methodology includes the interactive development of a system to say create functional applications in periods of short times, and in low budget, which was able to generate a web page with an aspect in the friendly interface, updated and according to the needs of the GAD and users. Descriptive Terms: reengineering, web page, GAD, RAP, Santa Fé, software